3(x+4)-2(x+2)=41

Simple and best practice solution for 3(x+4)-2(x+2)=41 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(x+4)-2(x+2)=41 equation:


Simplifying
3(x + 4) + -2(x + 2) = 41

Reorder the terms:
3(4 + x) + -2(x + 2) = 41
(4 * 3 + x * 3) + -2(x + 2) = 41
(12 + 3x) + -2(x + 2) = 41

Reorder the terms:
12 + 3x + -2(2 + x) = 41
12 + 3x + (2 * -2 + x * -2) = 41
12 + 3x + (-4 + -2x) = 41

Reorder the terms:
12 + -4 + 3x + -2x = 41

Combine like terms: 12 + -4 = 8
8 + 3x + -2x = 41

Combine like terms: 3x + -2x = 1x
8 + 1x = 41

Solving
8 + 1x = 41

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-8' to each side of the equation.
8 + -8 + 1x = 41 + -8

Combine like terms: 8 + -8 = 0
0 + 1x = 41 + -8
1x = 41 + -8

Combine like terms: 41 + -8 = 33
1x = 33

Divide each side by '1'.
x = 33

Simplifying
x = 33

See similar equations:

| 8*7=26-t | | 7x+1=12-5x | | 3x+8=3x-5 | | 8x-2(x-5)=x+25 | | 4k+13=26 | | 4d+-3=9 | | 2(x+5)-16=8 | | 5(x-6)+3=-7 | | 4x+10+3x=40-3x | | 2x+3y=15 | | 3(4x+6)=9x+12 | | 2(x+3)+3(x+2)=22 | | x-6(x+5)=15 | | 3x-x+8+5x-2=10 | | x(2x-9)=49 | | 6x-14x+16=-35+11 | | 3x+x-13+4-6x=12 | | 9-4x+7x=15 | | 0=6x-1 | | 3(2-x)=8(x-2) | | 15z-12=4z+2 | | 4x+3=-21 | | 2(x+1)=3(4-x) | | 2(x+3)-4=8 | | 2(a-4)+3=13 | | 5(x-4)+1=3x-1 | | 5x-6=-6(x+4)-26 | | 4f+1-2=5 | | 4(2x-1)=27+3(2x-5) | | 4f+1(-2)=5 | | 6y-2=3y-17 | | 18(x)(x)-10x-4=0 |

Equations solver categories